Catechol–TiO2 hybrids for photocatalytic H2 production and photocathode assembly12. Issue 94 (9th November 2017) - Orchard, Katherine L.; Hojo, Daisuke; Sokol, Katarzyna P.; Chan, Meng-Ju; Asao, Naoki; Adschiri, Tadafumi; Reisner, Erwin
Abstract : Charge-transfer dyes are explored for photocatalytic H2 evolution (DSP) and dye-sensitised photoelectrochemical applications (DSPEC). Abstract : Visible-light driven H2 evolution in water is achieved using catechol-photosensitised TiO2 nanoparticles with a molecular nickel catalyst. Layer-by-layer immobilisation of catechol–TiO2 onto tin-doped indium oxide electrodes generates photocathodic currents in the presence of an electron acceptor. This approach represents a new strategy for controlling photocurrent direction in dye-sensitised photoelectrochemical applications.